STUDY OF LIPID PROFILE AND NON-HDL CHOLESTEROL AS A BIOMARKER OF CARDIOVASCULAR RISK IN TYPE 2 DIABETES MELLITUS - PRAJAKTA R, WARJUKAR; SS, GHANGALE; CM, IYER (International Journal of Clinical and Biomedical Research, 2016)
Introduction: The reduction of cardiovascular risk by lowering low-density lipoprotein cholesterol (LDL-C) is well documented, and LDL-C remains the main target of lipid lowering therapy. However, not all patients with cardiovascular risk have elevated LDL-C. There is growing recognition that non-high density lipoprotein cholesterol (Non-HDL-C) is strongly related to cardiovascular risk. Aim: This study was done to evaluate the importance of Non-HDL C in predicting cardiovascular risk in type 2 Diabetes Mellitus. Methods: 100 type 2 diabetic patients were taken as subjects. Fasting and post meal blood sugar, lipid profile, and Non-HDL C was analysed in these patients. The patients were divided in two groups depending on their Non- HDL C level; ≤130 mg/dl and > 130mg/dl. Result and discussion: In this study it was seen that, age <60 years, being female, BMI >25 kg/m2 and LDL cholesterol >100mg/dl were associated with having Non-HDL cholesterol >130mg/dl. Conclusion: The results showed positive correlation between Non-HDL and LDL cholesterol. It also showed significant non achievement of Non-HDL cholesterol targets of ≤130mg/dl even if LDL cholesterol targets were achieved i.e. <100mg/dl suggesting the importance of measuring Non - HDL Cholesterol to predict the risk of cardiovascular disease in type 2 diabetes.